Study of the clothing needs of Metro Manila mountaineers when climbing Mt. Banahaw - Aganon, Ginger Y.; Mayo, Adelaida Villaraza (1995.)
Mounteneering is getting to be a popular sport of the times despite many accidents being reported in the newspapers and televisions. In Metro Manila alone, more than 100 mountaineering groups are organized and more than 75 are unorganized. One of the mountains most climbed by these mountaineers is Mt. Banahaw, in Quezon. Mt. Banahaw is one of the few high altitude mountains of Luzon which often climbed not only by mountaineering clubs but also by pilgrims and students. Mt. Banahaw has not been just any other mountain. It has always been thought as a mountain of so many characters. There are so many myths about Mt. Banahaw that are somehow connected to one religion or another but more to Catholicism. In almost each campsite of one of the major trails of Mt. Banahaw, there is a cross erected representing a station of the cross as in the Catholic rosary. This mountain also has so many caves in different routes that the people who lived there had declared each to have its own name and story. Other caves have been said to have a secret door and a secret word is they key to this door. Because of the many mysteries of Mt. Banahaw, many people climb it not only for religious cleansing like the pilgrims during Holy Week but also for fun and for educative purposes. Never the less, the most important things they have to bring when going through this mystic journey on Mt. Banahaw besides their food and water is their clothes. Clothing for climbing the trails of Mount Banahaw is definitely not as diverse as the food you can eat or the liquids you can drink. Any kind of food would keep you satisfied for your whole stay on the mountain as long as you bring enough. The same goes for food. When it comes to clothing, though, it is different. Clothing must conform with what activities you have to do while you are on the mountain and the amount you have to bring must also conform with the needs of climbing. This study was able to find out what kinds of clothes are most suitable to bring and wear as you climb the trails of Mount Banahaw. 50 People who have reached Mt. Banahaw's peaks at least once where asked to participate in the study as respondents. Only 44 of the respondents were able to qualify in the study. It was found out that all of the respondents wear a T-shirt for trekking combined with either cycling shorts of boxer shorts and of course socks. It was quite different when it comes to their clothes while in campsites. Most of the respondents still wear a T-shirt but others wear a long sleeve shirts and sweaters instead. Wind breakers were also combined with the other garments. More people wear leggings and jogging pants while in camp. When they reach the perks of Mt. Banahaw, it was obvious from the responses that more clothes were being used since this is where the temperature gets to be the coldest. More people wear T-shirts, combined with long sleeve shirts, sweaters. For their bottoms, leggings increases in use and jogging pants are also added to their layer of clothing. It was found out from the research that the system of clothing by most climbers was the layering method. It was also found out their system of layering is as follows, a mesh shirt at the very bottom, next would be a T-shirt, the a long sleeves, sweater, a wind breakers and depending on the weather, a rain jacket is added. For the bottoms, the following layering system is followed: cycling shorts, boxer shorts or leggings are used as the first layer then for the second layer jogging pants is used. Since layering is being practiced by most climbers, it was quite important to know the amount of clothing to bring. The questionnaire totaled the following: 4 T-shirts, 1 sweater, 1 mesh shirt, 1 long sleeves, 1 rain jacket, 1 leggings, 1 cycling shorts, 1 gloves and hat, 1 jogging pants, 1 boxer shorts, 1 wind breaker, 4 socks. It was also found out that the qualities of the clothing most advisable to bring has to be following: lightweight being the first priority, next being not bulky to bring and easy to dry, the next quality to consider is it being waterproof of warm to wear cool to wear, depending on the purpose, and lastly being absorbent of perspiration. Fashionable was not one of the most important qualities to consider according to the research. Wrinkle proof did not come out as any of the considerations. The basic clothing needs of climbers were mostly bought in their local department stores. While the special gears like the rain gears and cold gears are usually bought in the local department stores although more of the respondents answered that they buy their special gears in the United States and from the overruns of local exporters. It was also asked from the respondents if their rain gears and cold gears give them enough satisfaction. Most of the respondents answered that it was enough, some others said that they were pretty much satisfied and other were very satisfied. It was concluded that clothes for climbing Mt. Banahaw varied from your physical position of altitude in the mountain and the activities you are doing while you are there. But the main concern of the climbers when it comes to their clothing is their comfort.
Thesis (BSCT)--University of the Philippines Diliman.
Keywords: Mountaineers -- Philippines -- Clothing